2008
DOI: 10.1073/pnas.0809336105
|View full text |Cite
|
Sign up to set email alerts
|

CP1-dependent partitioning of pretransfer and posttransfer editing in leucyl-tRNA synthetase

Abstract: Mistranslation is toxic to bacterial and mammalian cells and can lead to neurodegeneration in the mouse. Mistranslation is caused by the attachment of the wrong amino acid to a specific tRNA. Many aminoacyl-tRNA synthetases have an editing activity that deacylates the mischarged amino acid before capture by the elongation factor and transport to the ribosome. For class I tRNA synthetases, the editing activity is encoded by the CP1 domain, which is distinct from the active site for aminoacylation. What is not c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

3
83
0

Year Published

2011
2011
2017
2017

Publication Types

Select...
4
2

Relationship

1
5

Authors

Journals

citations
Cited by 67 publications
(86 citation statements)
references
References 63 publications
3
83
0
Order By: Relevance
“…coli LeuRS harbors a tRNA-dependent pretransfer editing activity that is unmasked when its CP1 domain is deleted (21). We also found that we could activate pretransfer editing in E. coli LeuRS by incorporating an unchargeable 2′-deoxyadenosine tRNA Leu (2′dA-tRNA) (21).…”
Section: Resultsmentioning
confidence: 59%
See 4 more Smart Citations
“…coli LeuRS harbors a tRNA-dependent pretransfer editing activity that is unmasked when its CP1 domain is deleted (21). We also found that we could activate pretransfer editing in E. coli LeuRS by incorporating an unchargeable 2′-deoxyadenosine tRNA Leu (2′dA-tRNA) (21).…”
Section: Resultsmentioning
confidence: 59%
“…coli LeuRS harbors a tRNA-dependent pretransfer editing activity that is unmasked when its CP1 domain is deleted (21). We also found that we could activate pretransfer editing in E. coli LeuRS by incorporating an unchargeable 2′-deoxyadenosine tRNA Leu (2′dA-tRNA) (21). Thus, we hypothesized that the pathway to amino acid editing can shift between pre-and posttransfer editing mechanisms that are inherent to the enzyme (8,25).…”
Section: Resultsmentioning
confidence: 69%
See 3 more Smart Citations